TENSIONS AND CONTRADICTIONS IN BRAZILIAN AND VENEZUELAN SOCIETIES:: COMPARATIVE ANALYSIS OF PROTECTIVE LAWS FOR WOMEN'S HUMAN RIGHTS (Social and Environmental Law Journal, 2024)
This work aims to present the differences between the protective legislation for women in Brazil and Venezuela from the perspective of gender theory within the Inter-American human rights system. Latin America is the result of a civilizing process with historical similarities and differences in each country, but it was built on a similar structure of income concentration, inequality, and exclusion. In this context, women are part of minority groups that are most affected by this structure, violence, and numerous difficulties in accessing rights. Thus, the approach to examining the legal protection of women in the mentioned countries will be: presenting the Maria da Penha Law, a Brazilian law, and the Ley Orgánica sobre el derecho de las mujeres a una vida libre de violencia, a Venezuelan law, in relation to the current Constitution in each country; presenting the situation of these countries within the Inter-American human rights system; and analyzing the differences and similarities regarding violence against women in Brazil and Venezuela.
Keywords: Gender.; Human Rights.; Women's Protective Laws.